Chronotherapy in the treatment of oral pemphigus vulgaris: A case report - Mandavi Waghmare; Sejal S Puthenveetil (Wolters Kluwer Medknow Publications, 2021)
Oral vesiculobullous lesions are highly dynamic in their presentation making the current treatment strategies fall short of expected complete remission. With continuing research on the various treatment modalities of these lesions it is suggested that treating a disorder by following the biological and physiological behavior of the various bodily enzymes and hormones and their circadian rhythm helps in alleviating the symptoms faster with lesser or no side effects. This concept is termed "Chronotherapy." It works by timing the treatment with the intrinsic timing of illness.